2004
DOI: 10.1111/j.0269-8463.2004.00893.x
|View full text |Cite
|
Sign up to set email alerts
|

Patch–background contrast and patch density have limited effects on root proliferation and plant performance in Abutilon theophrasti

Abstract: Summary 1.We examined biomass and root proliferation responses of Abutilon theophrasti Medic. to the density of high nutrient patches and the patch-background contrast. Contrast in nutrient content between a patch and the background soil, as well as patch density, are important features of heterogeneous soil environments that have received little research attention. 2. Plants were grown in pots with no, one or two organic nutrient patches, and the equivalent nutrition of no, one or two patches in the backgroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 36 publications
(80 reference statements)
2
36
0
Order By: Relevance
“…Less data are available to test this prediction, although available data suggest this hypothesis may be supported. Lamb et al (20) found fewer roots were produced by plants as total habitat quality increased and when the total number of patches remained constant. However, there was only a nonsignificant trend toward reduced effort in patches as habitat quality increased (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Less data are available to test this prediction, although available data suggest this hypothesis may be supported. Lamb et al (20) found fewer roots were produced by plants as total habitat quality increased and when the total number of patches remained constant. However, there was only a nonsignificant trend toward reduced effort in patches as habitat quality increased (20).…”
Section: Discussionmentioning
confidence: 99%
“…Lamb et al (20) found fewer roots were produced by plants as total habitat quality increased and when the total number of patches remained constant. However, there was only a nonsignificant trend toward reduced effort in patches as habitat quality increased (20). Similar results have been found for competing plants that avoid areas of high competition in favor of root-free soil, where resource uptake is presumably higher (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NH 4 + and HPO 4 2− /H 2 PO 4 − or CO(NH 2 ) 2 and HPO 4 2− /H 2 PO 4 − , the later under optimal ammonification conditions) [2,5] and are poorly mobile in soil [6][7][8][9], crops can more efficiently acquire fertilizer-depot nutrients, thus improving their yields [4]. Nevertheless, it has been shown that intense rooting may not occur around fertilizer depots based on manure or mineral N under greenhouse and field conditions [10]; (Müller et al 2009, unpublished results). The reasons for this are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Selective root placement (also termed root foraging 'precision') is defined as the investment in roots placed into nutrient-rich zones, relative to root abundance in nutrient-poor zones. Selective root placement is ubiquitous among terrestrial species, but the benefits of this trait appear largely context-dependent, as species identity, nutritional composition of patches and duration of study influence the outcome (Hutchings and John 2004;Lamb et al 2004;de Kroon and Mommer 2006;Kembel et al 2008). This context-dependency exists for individually-grown plant species (Kembel and Cahill 2005), and also for plants under interspecific competition, where a high degree of selective root placement sometimes Robinson et al 1999), but not always, leads to the highest competitive ability (Bliss et al 2002;Cahill and Casper 1999;Rajaniemi 2007).…”
Section: Introductionmentioning
confidence: 99%